High-performance acousto-optic modulator based on environmentally favorable Ge20Sb15Se65 chalcogenide glass. Issue 21 (1st November 2021) - Ding, Shengjie; Dai, Shixun; Wu, Zhongchao; Cao, Zhenfei; Xu, Lulu; Wang, Min
Abstract: Acousto-optic (AO) properties of an environmentally friendly Ge20 Sb15 Se65 chalcogenide glass were investigated, and the results show that Ge20 Sb15 Se65 glass was a potential material for manufacturing AO modulator (AOM) because its composition possesses excellent performance of high optical quality and transmission in the infrared region spectral, non-toxic, high glass transition temperature, strong mechanical strength, easy to fabricate in large bulk, and isotropic homogeneity. Particularly, its outstanding AO figure of merit (M2 = 407 × 10 −15 s 3 /kg) was approximately 270 times that of fused quartz glass, making it attractive for AO device designs. Herein, the construction of the AOM based on Ge20 Sb15 Se65 glass as AO material was performed, and we obtained a high diffraction efficiency of 73.4% at a high acoustic frequency of 160 MHz and an extremely low radio-frequency (RF) power of 0.25 W when the laser beam at 1550 nm was controlled. To our best knowledge, the results of initial tests on the AOM prepared from Ge–Sb–Se chalcogenide glass were first reported. Such an AOM design enriches the family of AO devices and exploits the route for the practical application of chalcogenide glass.